The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3991/ijet.v17i14.31413
|View full text |Cite
|
Sign up to set email alerts
|

Learning Approaches Influence on College Students' Digital Literacy: The Role of Self-Determination Theory

Abstract: The development of digital literacy is believed to be achieved through individual learning and improvements. This study explored the mutual relations between college students' learning approaches and digital literacy by using Self-determination theory (SDT) from a psychological perspective. Structural equation modeling (SEM), part of a quantitative methodology, was designed with data collected through 639 students from three types of universities. SEM was used to verify the crucial indirect influence of SDT by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…Literasi digital merupakan kemampuan yang disebut sebagai literasi komputer, literasi teknologi informasi, literasi informasi, dan literasi media. Literasi digital juga mencakup kemampuan untuk mengakses, mengelola, memahami, mengintegrasikan, mengomunikasikan, mengevaluasi, dan menciptakan informasi secara aman dan tepat melalui teknologi digital (Law et al, 2018;Tian & Park, 2022). Literasi digital merupakan konsep penting untuk memahami teknologi, informasi, dan komunikasi.…”
Section: Hasil Dan Pembahasan a Literasi Digitalunclassified
See 1 more Smart Citation
“…Literasi digital merupakan kemampuan yang disebut sebagai literasi komputer, literasi teknologi informasi, literasi informasi, dan literasi media. Literasi digital juga mencakup kemampuan untuk mengakses, mengelola, memahami, mengintegrasikan, mengomunikasikan, mengevaluasi, dan menciptakan informasi secara aman dan tepat melalui teknologi digital (Law et al, 2018;Tian & Park, 2022). Literasi digital merupakan konsep penting untuk memahami teknologi, informasi, dan komunikasi.…”
Section: Hasil Dan Pembahasan a Literasi Digitalunclassified
“…Setap individu perlu memahami dan menyadai bahwa literasi digital merupakan kompetensi yang penting untuk dapat berpartsipasi di dunia digital saat ini (Andriopoulou et al, 2022;Tian & Park, 2022). Literasi digital sama pentingnya dengan kemampuan menulis, membaca, berhitung, dan kemampuan dasar lainnya.…”
Section: Hasil Dan Pembahasan a Literasi Digitalunclassified
“…Examining the nodes on the figure's perimeter that influence outcomes may yield more relevant information. Some nodes lack outbound linkages, suggesting that these factors, rather than behavioral intention, are the major focus of research (e.g., digital literacy [36], integration, reliability, assurance [37]). Overall, interested readers may uncover other intriguing patterns in the network that were not found in the study, or by analyzing information from Figure 7, e-learning researchers would have more alternatives for forming research hypotheses as opposed to depending on parsimonious models.…”
Section: Which Factors Served As Independent or Predictive Variables?...mentioning
confidence: 99%
“…Second, participants' actual level of DigComp was not assessed; this could affect the sincerity of data they provided (Koch et al, 2012). To overcome this limitation, an empirical study in which the researcher offers a realistic model or tools of how to incorporate digital education into pre-service teaching programmes is suggested; the results of Tian and Park's (2022) study concluded that neither universities nor societies can develop students' digital literacy in a traditional manner. Third, no explanation or causes were given by the participants Alnasib 108 that could enable the researcher to understand why they considered their pre-service teacher programme as fairly moderate in qualifying them for digital education.…”
Section: Limitations Strengths and Future Researchmentioning
confidence: 99%